Accessible and Secure Backpacks for Daily Use - Sudip Ray, Tanmayee Puntambekar, Mehuljeet Singh (International Journal of Modern Agriculture, 2020)
Backpacks are a staple for people to carry essentials on day to day life. Evolution of the backpacks have started from carrying essentials either in belt strap or bindles created from sticks and canvas. Modifications are seen within the backpacks used for photography, hiking and travelling, whereas there is minimal design upgradation of the backpack used on a daily basis. Current innovation in backpack includes solutions such as waterproofing, anti-theft, or posture correction design, on the other hand there is no popular modification for accessibility for the backpack in rush situations where backpack needs to be accessed while still on the back. Thus, this research paper focuses on problems faced by students and working professionals, while using backpacks on daily basis. Data was collected and assessed through triangulation method. Modification in security and accessibility will create a space for product development for daily use backpacks. More secure and easy to access backpacks will make the backpack functional for daily use.